MENGEMBANGKAN KOMPETENSI SOSIALDAN INTERPERSONAL ANAK DALAMPENDIDIKAN JASMANI - Soni Nopembri (Jurnal Pendidikan Jasmani Indonesia, 2006)
Kids often experience difficulties in their socialization process. These difficulties will influencetheir social skills. The difficulties in their socialization process could be a consequence ofthe poor up-bringing from their parents. The development in technological fields couldinfluence kid’s socialization process either, because there are so many hi-tech gameswhich unfortunately do not support the socialization process itself. The result which is intendedto be achieved from socialization process is a socially competent man. A man must haveskill, knowledge, and character to be functionable in his society and this could be achievedthrough social learning. Physical education allows kids to be included in social learningwith various physical activities that are in accordance with their growth and development.Playing and game are the real examples of socialization model for kids. Social andemotional expression will be poured down in playing and games activities. Physicaleducation at schools must be socially functionable in developing kid’s interpersonal andsocial competence through the learning it does. The need in using various learning methodsand models which support the development of social and interpersonal competence withoutput other aspects of the kids aside is highly urgent and significant.Keywords : Socialization, Physical Education.